Combining productivity and sustainability: A challenge for the new millenium - Anderson W.K. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Sustainability in agriculture contains economic, biological and social elements but the cornerstone is economic. Sustainable practices will not be employed in agriculture unless they can be paid for either at the farm or community level. Unless farmers are making secure profits they are unable to invest in sustainable practices, regardless of their desirability. Some approaches to increasing grain yield and grain quality to meet the demands of premium paying markets will be discussed. Some practices that are necessary for biological sustainability and that must be integrated into our cropping systems will also be discussed. They include:- soil type selection and management to restore fertility; pest, disease and weed management with minimum use of chemicals and; control of rising water tables and soil salinity through appropriate crop management and use of perennial species.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)